An empirical determination of the whole-life cost of FO-based open-loop wastewater reclamation technologies. (15th October 2019) - Jalab, Rem; Awad, Abdelrahman M.; Nasser, Mustafa S.; Minier-Matar, Joel; Adham, Samer; Judd, Simon J.
Abstract: Over the past 5–10 years it has become apparent that the significant energy benefit provided by forward osmosis (FO) for desalination arises only when direct recovery of the permeate product from the solution used to transfer the water through the membrane (the draw solution) is obviated. These circumstances occur specifically when wastewater purification is combined with saline water desalination. It has been suggested that, for such an "open loop" system, the FO technology offers a lower-cost water reclamation option than the conventional process based on reverse osmosis (RO). An analysis is presented of the costs incurred by this combined treatment objective. Three process schemes are considered combining the FO or RO technologies with membrane bioreactors (MBRs): MBR-RO, MBR–FO–RO and osmotic MBR (OMBR)-RO. Calculation of the normalised net present value (NPV/permeate flow) proceeded through developing a series of empirical equations based on available individual capital and operating cost data. Cost curves (cost vs. flow capacity) were generated for each option using literature MBR and RO data, making appropriate assumptions regarding the design and operation of the novel FO and OMBR technologies. Calculations revealed the MBR–FO–RO and OMBR-RO schemes to respectively offer a ∼20% and ∼30% NPV benefit over the classical MBR-RO scheme at a permeate flow of 10, 000 m 3   d −1, provided the respective schemes are applied to high and low salinity wastewaters. Outcomes are highly sensitive to the FO or OMBR flux sustained: the relative NPV benefit (compared to the classical system) of the OMBR-RO scheme declined from 30% to ∼4% on halving the OMBR flux from a value of 6 L m −2 . h −1 . Graphical abstract: Image 1 Highlights: Cost/NPV of wastewater (WW) reclamation by MBR-RO, MBR-FO & OMBR calculated/compared. Open loop systems considered: combined WW treatment & saline water osmotic dilution. Full-scale CAPEX data used; OPEX costs determined from semi-empirical expressions. NPV benefit 20% and 30% higher for OMBR & MBR-FO respectively cf. classical MBR-RO. Outcomes highly sensitive to assumed FO or OMBR sustainable net flux.